Risk-Taking Attitude among Management Students to Beckon Entrepreneurial Venture - Nagarajan, P.S., Chidambaram AL (International Journal of Advanced Science and Technology, 2019)
Entrepreneurs become a kingpin of every country’s growth manifested in various sectors that poises to hold it in global positions and showcase their significance in the global environment. This empirical research examines the Risk-taking attitude among management students to beckon entrepreneurial venture. The objective of this study is to identify the entrepreneurial risk bearing attitude among the management students and factors contributing to bear risk for initiating entrepreneurial venture. There are several factors such as; family, peer group, education and self confidence that wield a strong contribution towards risk bearing attitude of the managerial student to beckon entrepreneurial venture. Keyword:. Entrepreneur, Entrepreneurial venture, Risk-taking attitude, Risk bearing, self-confidence